Integrasi Ekoteologi dalam Pendidikan Kontekstual di Perguruan Tinggi Katolik: Suatu Kajian Paradigmatis - Suparman, Suparman (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2025)
This study defines ecotheology as a contextual educational paradigm. The paradigm is transformative and it aims to respond to the global climate crisis. The study focuses on Catholic religious higher education institutions in Indonesia. The study applied a conceptual-critical approach using multisite analysis across 13 Pastoral Colleges. The study explored theoretical foundations, pedagogical principles, institutional collaboration models, and designs ecotheological curriculum models that are locally relevant. The findings present ecotheology as a reflection of Christian faith. The reflection emphasizes the relationship between God, humanity, and creation. Ecotheology is implemented through three educational dimensions. The first dimension is scientific knowledge (episteme). The second dimension is moral-affective disposition (ethos). The third dimension is transformational practice (praxis). The implementation of ecotheological paradigms faces structural challenges. These challenges include curriculum fragmentation, limited resources, and conflicts among stakeholders. The study recommends educational policy reform, encourages sustainable and contextual educator capacity building, develop the holistic evaluation instruments. Theoretically, the study enriches the discourse on sustainable education. It introduces a normative dimension. This dimension links spirituality and ethics to ecological action. Practically, the study affirms the viability of ecotheology as a contextual educational paradigm. The paradigm shifts the focus of education. It moves from knowledge transfer to the formation of ecological change agents.